Analysis Of Passing Ability In Futsal Based On Leg Muscle Strength - Mardiana, Alfinta Khasanatin; Sistiasih, Vera Septi; Indarto, Pungki (Java Mutiara Media, 2025)
This study aims to examine how leg muscle strength and passing ability in futsal correlate with each other. The study sample consisted of 20 physical education students who actively participated in futsal. Passing ability and leg muscle strength tests were used to collect data. The results were tested for normality, linearity, and Pearson correlation. The results showed a significant relationship (p < 0.05) between lower limb muscle strength and passing ability; a correlation coefficient of 0.611 indicates a strong correlation. This suggests that good lower limb muscle strength, such as strength, balance, and coordination, significantly influences the ability to master passing techniques.